Record of a nonbarred clastic shoreline - Isla, Manuel Fermín (2020)
The morphology of wave-dominated clastic shorelines (i.e., foreshore and upper-shoreface sediments) can vary from barred to nonbarred, though the ancient record of nonbarred, sand-dominated shorelines has yet to be recognized. Here, a facies and quantitative architectural analysis of a clastic succession characterized by sandy inclined beds is presented and interpreted as the record of a high-gradient, nonbarred shoreline. Inclined beds dip seaward, have a tangential geometry (<3 m height, <40 m length, <11° dip), and are composed of planar lamination along the foresets and subordinate small-scale trough cross-bedding in the bottomsets. This facies distribution reflects a steep beach profile with a narrow surf zone and the development of plane beds both in foreshore and proximal upper-shoreface settings. Successive packages of inclined beds (a few tens of meters wide) are interpreted as the seaward accretion of this shoreline morphology, producing distinctive architectural elements (foresets and bottomsets). For the first time, we propose diagnostic criteria for identification in the rock record of the widely used modern nonbarred clastic shoreline model, and we contrast them with classical facies models of barred systems. Moreover, we discuss similarities and differences with radar-based Holocene coastal architectural elements, highlighting the need to incorporate detailed two-dimensional quantitative studies for refining the reconstruction of deep-time and recent clastic shorelines.